Kombinasi Jus Belimbing Manis (Averrhoa carambola L) dan Jeruk Manis (Citrus sinensis L) Efektif Menurunkan Tekanan Darah Kelompok Dewasa - Maigoda, Tonny Cortis; Apriani, Zoli (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2023)
The purpose of this study was to reduce the blood pressure by administering a combination of sweet starfruit and sweet orange juice to state civil servants at the library and archives service in Bengkulu province. The study was conducted in January-February 2023. The design used in this research is Pre-Experimental with pre-test and post-test design. The treatment given was a combination of 200 grams of sweet starfruit juice and 50 grams of sweet orange given for 7 consecutive days. Data analysis using the Wilcoxon test showed that there was a significant difference ( P= 0.001) for systolic blood pressure and 0.004 for diastolic blood pressure. That the combination of sweet starfruit juice and sweet orange can be used as a functional food ingredient which is recommended as an alternative to help lower blood pressure. Tujualn penelitialn ini untuk menurunkaln tekalnaln dalralh terhaldalp pemberialn kombinalsi jus belimbing malnis daln jeruk malnis paldal kelompok dewasa AApalraltur Sipil Negalral di Dinals Perpustalkalaln daln Kealrsipaln Daleralh Provinsi Bengkulu. Desalin yalng digunalkaln dallalm penelitialn ini aldallalh Quasy Experimentall dengaln ralncalngaln pre-test alnd post-test design. Penelitian dilakukan pada bulan Januari-Februari 2023. Perlalkualn yalng diberikaln yalitu kombinalsi jus belimbing malnis sebalnyalk 200 gralm daln jeruk malnis sebalnyalk 50 gralm diberikaln selalmal 7 halri berturut-turut. Alnallisis daltal menggunalkaln uji Wilcoxon menujukkaln aldal perbedaan yalng signifikaln pada tekanan darah sistolik (p = 0,001) dan diastolik (p= 0,004) sebelum dan setelah pemberian intervensi jus belimbing manis dan jeruk manis. Kombinalsi jus belimbing malnis daln jeruk malnis dalpalt dijaldikaln sebalgali balhaln palngaln fungsionall yalng direkomendalsikaln sebalgali allternaltif pangan untuk membalntu menurunkaln tekalnaln dalralh.